Influence of host immunoregulatory genes, ER stress and gut microbiota on the shared pathogenesis of inflammatory bowel disease and Type 1 diabetes. (December 2013) - Gjymishka, Altin; Coman, Roxana M; Brusko, Todd M; Glover, Sarah C
Inflammatory bowel disease (IBD) with its two distinct entities, Crohn's disease and ulcerative colitis, and Type 1 diabetes mellitus (T1D) are autoimmune diseases. The prevalence of these diseases continues to rapidly rise in the industrialized world. Despite the identification of several genetic loci that are associated with both IBD and T1D, thus far, there is a paucity of epidemiological data to support a clinical overlap. In an effort to better understand the underlying pathogenic mechanisms of both IBD and T1D, this review summarizes the literature about these related autoimmune diseases, describes the most recent advances in their etiopathogenesis and emphasizes the genetic and nongenetic factors that exercise a differential influence. Genome-wide association studies have identified genetic loci with a role in immune response regulation that are linked to both IBD (particularly Crohn's disease) and T1D. Some of these genetic loci (e.g., IL-18RAP ) have a divergent role, conferring risk for one disease and protection for the other. Recent evidence highlights an important role of gut microbiota and cellular responses (e.g., endoplasmic reticulum stress) in the pathogenesis of both IBD and T1D.